Continuing Decrease in Hepatitis B Virus Infection 30 Years After Initiation of Infant Vaccination Program in Taiwan - Ni, Yen-Hsuan; Chang, Mei-Hwei; Jan, Chyi-Feng; Hsu, Hong-Yuan; Chen, Huey-Ling; Wu, Jia-Feng; Chen, Ding-Shinn (Clinical gastroenterology and hepatology, 2016)
Taiwan began a universal hepatitis B virus (HBV) vaccination program for infants in July 1984. The seroprevalence of hepatitis B surface antigen (HBsAg) decreased from 9.8% before the vaccination program to less than 1% by 25 years afterward. We continued to monitor HBV infections in this population. We conducted a series of serologic and epidemiologic surveys in the Taipei metropolitan area every 5 years from 1984 through 2014. From January 1 through December 31 of 2014, we collected serum samples from 4605 apparently healthy individuals (ages: 287 were <3 y, 405 were 3–6 y, 675 were 7–12 y, 686 were 13–18 y, 468 were 18–22 y, and 2084 were 22–50 y). All subjects were tested for HBsAg, its antibody (anti-HBs), and hepatitis B core antibody (anti-HBc). We performed genotype and viral load analyses for patients who tested positive for anti-HBc. Of vaccinated participants (age, <30 y; n = 3299), 0.5% tested positive for HBsAg, 47.4% tested positive for anti-HBs, and 4.5% tested positive for anti-HBc. Of unvaccinated participants (age, 30–50 y, n = 1306), 6.7% tested positive for HBsAg (P < .0001), 69.4% tested positive for anti-HBs, and 44.1% tested positive for anti-HBc. One occult HBV infection was found in each age group. Among subjects positive for HBsAg younger than age 30, 77% were born to mothers positive for HBsAg. Based on a series of serologic and epidemiologic surveys performed in the Taipei metropolitan area, 6.7% of persons born before the universal HBV vaccination program were positive for HBsAg, compared with 0.5% of those born afterward. Most subjects positive for HBsAg younger than age 30 were born to mothers positive for HBsAg.